Microcredit and Gendered Pathways to Inclusive Growth: Evidence from Women Entrepreneurs in Rural and Urban Nigeria - Egbetokun, Samuel Olurotimi (NIU Journal of Educational Research, 2025)
Eliminating deep-rooted gender inequality in access to finance and productive resources is a key issue that requires consideration when promoting inclusive growth in Nigeria. This paper analyzes how microcredit has affected the entrepreneurial performance of women in rural and urban areas, with a specific focus on the generation of income, the survival of the business, and domestic welfare. Using a mixed-method design, which includes survey data collected in the microfinance institutions and a qualitative interview, the study examines the contextual variables, social networks, and institutional intermediaries that mediate the impacts of small-scale credit. The evidence shows that microcredit would enable women to expand their businesses, accumulate assets, and make independent decisions, especially in urban areas where market connectivity and financial literacy are relatively high. On the other hand, women in rural areas still face the structural disadvantages of a high cost of transactions, inefficient collateral, and inadequate institutional coverage that reduce the developmental advantage that should be enjoyed through microfinance. The comparison of these two opposing courses of action leads to the suggestion that inclusive growth cannot be achieved by simply providing credit, but rather by the creation of gender sensitive financial systems, enhancing rural infrastructure, and continuing institutional reforms. When placed within the larger context of development in Nigeria, the study provides novel empirical information on the gendered processes in which financial inclusion can revolutionize the economy regarding equity and sustainability. Keywords : Gender, Inclusive Growth, Microcredit, Women Entrepreneur